Effect of Age at Slaughter on Various Carcass Characteristics of Hassan Sheep - Shanthesha, Kandikere M; Ruban, Savariraj W; Guruprasad , Rachaiah; Shivappanayaka, Honnebagi B; Naveen, Kumar S; Shivakumar, Rekhyanaik; Sudarshan, Siggiriyappa (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out to evaluate the influence of age at slaughter on various carcass characteristics of Hassan sheep. A total of 32 male Hassan sheep 12 each in 3 different age groups, viz., 6-8 months (T1), 12-15 months (T2) and 30-32 months (T3) were slaughtered as per standard procedure. The pre-slaughter weight (PSW), hot carcass weight (HCW), dressing percent (DP) and loin eye area (LEA) revealed a significant difference (p
Keywords: Age at slaughter; Dressing per cent; Hassan sheep; Primal cuts